The Effectiveness of Web 2.0 Tools Training Workshop Using Canva and Figma in Developing Creative Visual Content - Ibrahim, Norshahila; Chandra, Albert Yakobus; Saari, Erni Marlina; Prasetyaningrum, Putri Taqwa; Pratama, Irfan (Asian Journal of Assessment in Teaching and Learning, 2023)
Due to its accessibility, convenience, and capacity to meet a variety of learner needs, web tools have become increasingly popular as a way to acquire these abilities. However, there is lack of study on the efficacy of web tools in fostering creativity and the role that web tools play in this process. It prompts to critically examine whether these virtual learning environments are genuinely successful in cultivating creative skills and, if they are, how web tools function as catalysts for their effectiveness. Thus, this paper aims to investigate the effectiveness of web 2.0 tools using Canva and Figma in enhancing creativity in the domain of visual content creation. The methodology was adapted and modified from the Kirkpatrick's evaluation model, focusing on four key levels: (1) Reaction, (2) Learning, (3) Behavior, and (4) Results. The participants for the training were undergraduate students from Universiti Pendidikan Sultan Idris dan Universitas Mercu Buana Y.ogyakarta The research design involves a multi-dimensional assessment that includes survey, and pre-test and post-test. The study findings indicate that graphic design web tools significantly contribute to the development of creativity in visual content. The lowest mean score value for the training is 4.26 and the highest mean score value is 4.48. The analysis highlights that the participants experienced notable improvements in their creative skills after completing the training, with an increase in the quality and diversity of their visual content. The adapted evaluation model provides a holistic understanding of the impact of digital learning on participants, including their reactions, the knowledge acquired, changes in creative behavior, and the tangible outcomes of their creative endeavors.